Intrapartum Intrauterine Fetal Demise with Normal Umbilical Cord Blood Gas Values at Birth - Michael D. Benson (Case Reports in Obstetrics and Gynecology)
A case is presented in which a fetus was delivered by cesarean section for failure to progress and a “nonreassuring heart rate tracing” in which the Apgar scores were unexpectedly 0 at 1, 5, and 10 minutes. Resuscitation was unsuccessful after 30 minutes. The venous cord gas was normal and the arterial blood gas was not consistent with intrapartum asphyxia. At the time of surgery, the placenta appeared grossly normal. The autopsy was entirely normal. This case raises questions about our understanding of intrauterine fetal demise and suggests an approach to future research.